2020
DOI: 10.1155/2020/4806987
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Robotic Arm-Assisted Knee Surgery: The First Attempt to Use the System for Knee Revision Arthroplasty

Abstract: Robotic arm-assisted arthroplasty was introduced in 2006 and has expanded its applications into unicompartmental knee, total knee, and total hip replacement. The first case of a revision surgery from conventional unicompartmental to total knee arthroplasty with the utilization of the robotic arm-assisted MAKO system is presented. An 87-year-old female presented with deteriorating left knee pain due to failure of medial unicompartmental knee arthroplasty at the outpatient clinic. The patient was advised to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…In total hips, the computer-based software allows the surgeon to individualize the cup inclination/version, thereby decreasing dislocation rates [ 25 ]. Previous studies have shown that the robotic-arm assistance can be used for the conversion of UKA to TKA as well as previous hip fusion to THA [ 12 , 13 ]. To our knowledge, this is the first report of this technology being used for revision of a total knee replacement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In total hips, the computer-based software allows the surgeon to individualize the cup inclination/version, thereby decreasing dislocation rates [ 25 ]. Previous studies have shown that the robotic-arm assistance can be used for the conversion of UKA to TKA as well as previous hip fusion to THA [ 12 , 13 ]. To our knowledge, this is the first report of this technology being used for revision of a total knee replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons continue to harness the abilities of robotics and devise ways to use new technology during surgery. There are case reports of the robot being used in the conversion of UKA to TKA, as well as conversion of previous hip fusion to THA [ 12 , 13 ]. Advanced imaging is frequently used for preoperative planning, which can be helpful in the restoration of native anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…There is a paucity of literature on robotic-assisted rTKA including just one case report [ 7 ] and one retrospective review [ 8 ]. All previous studies demonstrated the use of robotics in conversion of failed UKA to TKA.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, robotic techniques have promising applications in orthopedic surgery. In recent years, robotic technology has matured gradually, with an increasing number of surgical robots obtaining approval from the Food and Drug Administration for clinical practice [5][6][7][8]. Some reports found that robotic surgery is more accurate in orthopedic implant placement, results in less intraoperative radiation exposure, as well as postoperative bleeding and pain, and has a better prognosis compared with conventional freehand techniques [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%